The Effect of the Project Based Learning Model on the Reading Comprehension Ability of Students in Grade V of SD Negeri 101600 Purba Bangun - Irma Sari Harahap; Zunidar (AT-THULLAB : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This study investigates the effect of the Problem-Based Learning (PBL) model on the reading comprehension skills of fifth-grade students at SDN 101600 Purbabangun, a public elementary school located in Sukamulia, Padang Lawas Utara Regency, North Sumatra Province. In this school, many students demonstrate fluency in reading but face difficulties in comprehending texts critically. The research employed a quantitative approach using a quasi-experimental method with a nonequivalent control group design. A total of 40 fifth-grade students were selected through purposive sampling and divided into two groups: an experimental group taught using the PBL model and a control group taught using conventional methods. Data were collected through pre-tests, post-tests, classroom observations, and student response questionnaires. An independent sample t-test was used for data analysis at a 5% significance level. The results showed a significant difference in reading comprehension between the two groups, with a p-value of 0.0424 (p < 0.05). These findings demonstrate that the PBL model effectively enhances students’ reading comprehension, particularly in developing their critical thinking and problem-solving skills. The study emphasizes the need for innovative and student-centered learning approaches to address reading challenges in elementary schools.